2013
DOI: 10.1001/jamapsychiatry.2013.36
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of National Implementation of Prolonged Exposure Therapy in Veterans Affairs Care

Abstract: osttraumatic stress disorder (PTSD) affects more than 6% of the US population and up to 13% of US military personnel returning from deployment in Iraq and Afghanistan. 1-3 It is associated with substantially reduced quality of life through both impaired role functioning and higher risk of cardiovascular disease, diabetes mellitus, and substance use conditions. 4-8 There is an especially critical need for effective treatments for PTSD as increasing numbers of veterans return from Iraq and Afghanistan. Since 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
287
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(331 citation statements)
references
References 35 publications
30
287
4
Order By: Relevance
“…Most mental health practitioners who use it view it as the only effective and reliable procedure to allay the mentally crippling symptoms of PTSD and related syndromes (60, 156,535). The major problems with exposure therapy have been listed by Singewald et al (602): "A significant proportion of patients either 1) have difficulties bearing the demanding and exhausting process of this therapy; 2) do not, or not sufficiently, respond to the therapy -failing to substantially reduce their fear responses; or 3) respond initially, but suffer from return of fear phenomena hampering remission and full recovery" in spite of it being the best or the only effective treatment for PTSD and for other major disturbances involving fear memory.…”
Section: Fear Extinction and Its Relation With Exposure Therapy Fomentioning
confidence: 99%
“…Most mental health practitioners who use it view it as the only effective and reliable procedure to allay the mentally crippling symptoms of PTSD and related syndromes (60, 156,535). The major problems with exposure therapy have been listed by Singewald et al (602): "A significant proportion of patients either 1) have difficulties bearing the demanding and exhausting process of this therapy; 2) do not, or not sufficiently, respond to the therapy -failing to substantially reduce their fear responses; or 3) respond initially, but suffer from return of fear phenomena hampering remission and full recovery" in spite of it being the best or the only effective treatment for PTSD and for other major disturbances involving fear memory.…”
Section: Fear Extinction and Its Relation With Exposure Therapy Fomentioning
confidence: 99%
“…Multiple studies have been conducted with combat veterans in the VA system (Eftekhari et al, 2013;Goodson et al, 2013;Rauch et al, 2009;Tuerk et al, 2011;Yoder et al, 2012). All of the effectiveness studies carried out with vetrans have shown that PE is an effective treatment for PTSD.…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
“…All of the effectiveness studies carried out with vetrans have shown that PE is an effective treatment for PTSD. Eftekhari et al's (2013) study is noteworthy because it evaluated the national implementation of PE throughout the VA system and included a sample of over 1900 veterans. An important finding from Yoder et al's (2012) study was that Persian Gulf War veterans responded significantly less well to treatment than both…”
Section: Psychotherapies For Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to prolong the exposure until the anxiety reduces [22]. In one of the studies regarding a PE's ef icacy, it has been shown to be effective in 60% of veterans [23].…”
Section: Prolonged Exposure (Pe)mentioning
confidence: 99%